The Pharmacoresistant Epilepsy: An Overview on Existent and New Emerging Therapies - Fattorusso, Antonella; Matricardi, Sara; Mencaroni, Elisabetta; Dell'Isola, Giovanni Battista; Di Cara, Giuseppe; Striano, Pasquale; Verrotti, Alberto (Frontiers in Neurology, 2021)
Epilepsy is one of the most common neurological chronic disorders, with an estimated prevalence of 0.5%-1%. Currently, treatment options for epilepsy are predominantly based on the administration of symptomatic therapy. Most patients are able to achieve seizure freedom by the first two appropriate drug trials. Thus, patients who cannot reach a satisfactory response after that are defined as pharmacoresistant. However, despite the availability of more than 20 antiseizure medications (ASMs), about one-third of epilepsies remain drug-resistant. The heterogeneity of seizures and epilepsies, the coexistence of comorbidities, and the broad spectrum of efficacy, safety, and tolerability related to the ASMs, make the management of these patients actually challenging. In this review, we analyze the most relevant clinical and pathogenetic issues related to drug-resistant epilepsy, and then we discuss the current evidence about the use of available ASMs and the alternative non-pharmacological approaches.